Phytochemical screening, quantitative determination of phenolic compounds, and antioxidative activity of Ostrya carpinifolia - Starčević, Mirsada; Subašić, Mirel; Pustahija, Fatima (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2017)
Ostrya carpinifolia is an interesting and suitable species for reforestation and landscaping.For the first time ever, phenolic profile, antioxidative and antimicrobial activity of O. carpinifolia was done in this study. Aqueous and methanol extracts of the aerial parts were analyzed using either fast screening methods of secondary metabolites, and UV/VIS spectrophotometry for determination of polyphenolic contents and antioxidant activity (DPPH). Antimicrobial activity of methanol extracts was investigated using the disc diffusion method against a selected nine microorganisms. Phytochemical tests confirm the presence of cardiac glycosides, coumarins, emodins, flavonoids, tannins, terpenes, terpenoids and steroids, while anthocyanins, fatty acids and saponins were absent in all aqueous extracts. Leucoanthocyanins were observed only in the stem extract. Methanol extracts of leaves contain the highest level of total phenolics and flavonoids (35.574 and 30.908 mg CE g-1 DW, respectively), while the inflorescences extracts were the richest with total proanthocyanidins and phenolic acids (19.165 mg CE and 9.342 mg CAE g-1 DW, respectively). All methanol extracts showed very strong antioxidative activity, where the lowest activity was recorded for inflorescences (IC50: 0.242 mg mL-1) and the highest for stem (IC50: 0.107 mg mL-1). Analyzed extracts showed no antimicrobial activity against the test organisms. ANOVA indicated the presence of significant differences between the total phenolics and flavonoids and DPPH (p<0.05). Duncan’s test confirmed the presence of statistically significant and very high positive correlation (R=0.989) between total phenolics and phenolic acids contents. Obtained results indicate the necessity of further research of European hop-hornbeam..